2022
DOI: 10.3389/fimmu.2022.835345
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-Primed hUCMSCs Significantly Reduced Inflammation via the Foxp3/ROR-γt/STAT3 Signaling Pathway in an Animal Model of Multiple Sclerosis

Abstract: Our previous study showed that interferon gamma (IFN-γ) might enhance the immunosuppressive properties of mesenchymal stem cells (MSCs) by upregulating the expression of indoleamine 2,3-dioxygenease. Therefore, we treated experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis (MS), with IFN-γ-primed human umbilical cord MSCs (IFN-γ-hUCMSCs). This study aimed to investigate the potential therapeutic effects of IFN-γ-hUCMSCs transplantation and to identify the biological path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The body weight was considerably higher and the clinical score reached zero on the last five days of the study in mice treated with IFN-γ-licensed MSC. In accordance with our data, the preventive impacts of the IFN-γ-exposed MSCs on body weight loss and EAE-related clinical scores were indicated 34 51 . It has also been reported that priming of MSCs with IFN-γ significantly improves the efficacy of MSC to reduce graft-versus-host disease (GVHD) mortality in mice 27 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The body weight was considerably higher and the clinical score reached zero on the last five days of the study in mice treated with IFN-γ-licensed MSC. In accordance with our data, the preventive impacts of the IFN-γ-exposed MSCs on body weight loss and EAE-related clinical scores were indicated 34 51 . It has also been reported that priming of MSCs with IFN-γ significantly improves the efficacy of MSC to reduce graft-versus-host disease (GVHD) mortality in mice 27 .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the MOG-stimulated lymph node cells and the MOGstimulated splenocytes from EAE mice treated with IFN-γ-induced MSCs produced lower levels of IFN-γ and IL-17, whereas secrete higher levels of IL-4 and IL-10 compared with control cells from non-induced MSC-treated mice [34]. Thus, IFN-γ-induced MSCs can improve the Th17/Treg and Th1/Th2 imbalances in EAE mice [34]. The results from an in vitro experiment also indicated that IFN-γ promotes the capacity MSCs to induce Treg cell differentiation [55].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Further, the activation of STAT3 signaling, a downstream effector of the ERK pathway, is also regulated by MDL 72527 treatment. STAT3 signaling is demonstrated to be a major player in EAE-induced [ 79 ] tissue damage [ 93 , 94 , 95 , 96 , 97 ]. The impact of MDL 72527 indicated in the present study supports the potential of SMOX inhibition in reducing inflammation, in addition to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%